Plumage brightness and uropygial gland secretions in barn swallows. Issue 2 (31st May 2018) - Pape Møller, Anders; Mateos-González, Fernando
Abstract: The uropygial gland has been hypothesized to play a role in sexual signaling through a "make-up" function derived from the effects of secretions from the gland on the appearance of the plumage and bare parts of the body. Here we show that plumage brightness of dorsal feathers of individual barn swallows Hirundo rustica was greater in mated than in unmated individuals. In addition, plumage brightness increased with colony size. Furthermore, plumage brightness was positively correlated with the amount of wax in the uropygial gland, negatively correlated with time of sampling of uropygial wax (perhaps because more wax is present early in the morning after an entire night of wax production without any preening), and negatively correlated with the number of chewing lice that degrade the plumage. Experimentally preventing barn swallows from access to the uropygial gland reduced plumage brightness, showing a causal link between secretions from the uropygial gland and plumage brightness. These findings provide evidence consistent with a role of uropygial secretions in signaling plumage brightness.